6p+20q+6=

Simple and best practice solution for 6p+20q+6= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6p+20q+6= equation:


Simplifying
6p + 20q + 6 = 0

Reorder the terms:
6 + 6p + 20q = 0

Solving
6 + 6p + 20q = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + 6p + -6 + 20q = 0 + -6

Reorder the terms:
6 + -6 + 6p + 20q = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 6p + 20q = 0 + -6
6p + 20q = 0 + -6

Combine like terms: 0 + -6 = -6
6p + 20q = -6

Add '-20q' to each side of the equation.
6p + 20q + -20q = -6 + -20q

Combine like terms: 20q + -20q = 0
6p + 0 = -6 + -20q
6p = -6 + -20q

Divide each side by '6'.
p = -1 + -3.333333333q

Simplifying
p = -1 + -3.333333333q

See similar equations:

| 0.3(n-5)=0.4-2(n-7) | | 10(7-x)=0 | | X(2y+3)+x(5y+4)= | | 0.05x+0.20y=4.20 | | 6(2x-3)/4=16-(-18) | | .1x+1.4=.3 | | 6a^2-2c+2a^2-2c^2= | | x^2+28x+21=0 | | (T+4)+(t+3)+(t-1)=39 | | -3+14=m-8 | | (1k+12)(3k-2)= | | 25a=23 | | 27x+23=-4 | | 27x+13=-4 | | x^2-4x+y^2+10y+18=0 | | -6a-43=25 | | 27x+18=-4 | | 11x-2x=2x+10 | | 4(x-7)=x+5 | | 3e^5x-4=19 | | 59/8 | | 8.5+1.4(I-U)=F | | 5(w-6)-8w=-9 | | log(x+9)=1-log(x-8) | | 5x+4=3x-3x+4 | | (7*6-7-1)= | | D=5-(-7) | | 4*6-3-1= | | 2-16/x^3=0 | | r^2+16r-83=-3 | | a+a+2b= | | 65-m=H |

Equations solver categories